Psychological and Social Factors Affecting Eating Habits in Adolescent (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2022)
Eating behavior is a means or what a person continuously as the characteristics of the individual in meeting the needs, both physiologically, socially and emotionally to food to meet the need of nutrition for the body. The purpose of this literature study is to examine and explore psychological and social related factors that influence eating habits in adolescents. The method used is a literature study using eight relevant research journals as the main reference. The results of this study, it was found that psychological and social factors can affect eating habits in adolescents. Adolescent psychology will be greatly influenced by the social environment of adolescents such as from the family environment, school environment, peers, culture, health status and also the economy. The wrong eating habits of adolescents can lead to eating disorders and nutritional problems in adolescents. Psychosocial factors are known to greatly influence the changes in eating habits in adolescents. Changes in eating habits due to these factors will lead to nutritional problems in adolescents.